A systematic review of the uses and spread of corpora and data-driven learning in CALL research during 2011–2015. Issue 1 (27th January 2022) - Pérez-Paredes, Pascual
Abstract: This research uses the theoretical framework of CALL normalisation developed by Bax (2003 ) and Chambers and Bax (2006 ) to offer a systematic review (Gough et al., 2012 ) of the uses and spread of data-driven learning (DDL) and corpora in language learning and teaching across five major CALL-related journals during the 2011–2015 period. DDL research represented 4.2% of all published papers on CALL during this time frame. The main focus of research was found to be the use of concordancing and collocations when developing university students' writing skills. Contrary to previous research, access to technology was not identified as an impeding factor for normalisation. Syllabus integration and a lack of contribution from language teachers other than researchers emerged as threats to the normalisation of corpora use. Further theorisation is needed if DDL and corpora are to expand their influence on mainstream second language education.